Impact of dysfunctional conflict in public organization: A case study of COASCO - Mallan, Mbwana O. (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a fulfillment of the requirements for award of the Master Degree of Business Administration (MBA-CM) of Mzumbe University